The exposure assessment of airborne particulates for indoor and outdoor environment of International Islamic School Gombak Selangor, Malaysia - Djabir, Djabir Abdoulaye (Kulliyyah of Architecture and Environmental Design, International Islamic University Malaysia, 2018)
Indoor air quality is one of the major problems needs to be address within the building design it is far more complex issue than other environmental challenges. Bad indoor air quality (IAQ) may affect human health and cause many health problems especially for young people due to weakness of their organs and it will be a more critical issue after a long period of time. The objective of this research is to determine the mass concentration level of airborne particles that affect the indoor and outdoor of the schools and to measure the level of airborne particles within the guidelines and standards of IAQ in Malaysia and other Asian countries. To know the impact associated with air borne particles among children learn in school. This research cover it by several stapes of primary data collection (case study, site survey, interview and questionnaire survey) and other sources such as literature review. The school selected for the case study is the International Islamic School of Malaysia in the Gombak area. The result shows that the mass concentration on level of airborne particles within the area of the school has exceed the permission limit of 0.15 mg /m³ by the Code of practice for 2005 by Department of Safety and Health (DOSH), Malaysia and more than the standard stated by The Department of Environmental (DOE) . After eight hours of sampling This research finds the total average ratio of respirable divide to inhalable airborne particulates for outdoor ratio is 0.848 (traffic light ) and for 0.696 (school canteen and for indoor ratio is 0.409 ( Biological lab ) and 0.751 for ( Class Arif 1) . This is due to regular traffic in the school area and that because it is near to the main road and so close to open area of the school canteen. This could bring symptoms and other health problems during traffic between 9 am and 10 am. This is because of the proximity of the highway to the school building and that will increase the percentage and average of mass concentration in the school environment. Due to that it is highly recommended to implement the Malaysian standard and guidelines for indoor and outdoor air quality in order to avoid the high risk of Air borne particles